Porous anisotropic metal nanostructures through controlled transmetallation across a dialysis membrane - Shukla, Sourabh; Pasricha, Renu; Sastry, Murali (Journal of Nanoscience and Nanotechnology, 2009)
Nanostructured metals with hollow interiors are of technological importance due to their unique optoelectronic properties and enhanced surface area. We describe herein, a novel method for the synthesis of anisotropic gold and palladium nanoparticles through a simple galvanic replacement reaction across a semi-permeable dialysis membrane. The control over the reaction kinetics achieved by the presence of membrane enables one to tune the bimetal composition, particle porosity and morphology. Rapid outward diffusion of silver ions generated from the sacrificial silver nanoparticles even at room temperatures prevents the precipitation of high quantities of silver chloride, thereby circumventing the need for product purification. The porous anisotropic nanostructures have potential applications in catalysis, cell imaging and therapeutics.
Keywords: Ag/Pd Nanostructures; Anisotropic Nanoparticles; Dialysis; Galvanic Replacement; Porous nanostructures; Silver Nanotriangles; Silver Nanowires; Transmetallation